Socio-demographic characteristics of the addicted inmates of Qom and Tabriz prisons in Iran - Sattari Mohammadreza; Islambulchilar Mina; Toluyi Mohsen; Mashayekhi Siminozar (Tabriz University of Medical Sciences, 2012)
Purpose: The aim of this investigation was to study the factors responsible for drug addiction amongst the inmates of Tabriz and Qom prisons, to further understand the reasons for drug abuse particularly in the young and find improved methods for combating these widespread problems. Methods: A multi-choice questionnaire was provided to inmates to potentially assess the reasons for their drug addiction psychiatric, personal, social, economical, and political factors were thought to be implicated. Two hundred drug addicted prisoners were individually interviewed randomly in both Tabriz and Qom prisons. A questionnaire including questions about the inmates' demographic characteristics and 49 multiple answers questions, was provided to identify the effects of different reasons for drug addiction for instance: psychiatric, personal, social, economical, and political factors. The collected data were analyzed by Student t-test and chi-squared test using SPSS software. Results: The results showed that the following factors could lead to drug addiction e.g. company with addicted friends and offenders, curiosity, imitation, illiteracy, family problems, crowded family, poverty, unemployment, and lack of self confidence. There were significant differences between Tabriz and Qom prisoners in relation to age, starting age of addiction, job, income, education, class of addiction, marital status, and hobbies. Mean age, mean starting age of addiction, poverty, alcohol drinking before addiction, marital status, heroin addiction, codeine and benzodiazepines abuse were significantly greater for Tabriz prisoners than those of Qom. Conclusion: It is clear that the governmental programs for reducing unemployment, creation of safe hobbies, proper control on drug dispensing in the pharmacies, proper birth control programs, and encouragement to higher education could alleviate addiction problem in Iran.